Decoding the Behavioral Intentions of Gen Z Investors: Analysing the Impact of Investor Protection in the Digital Era & Predictive Insights from PLSpredict - Gokhale, Gautam Milind; Mittal, Ankur (International Journal of Economics and Financial Issues, 2025)
This study aims to examine the impact of investor protection measures on generation Z (GenZ) investors behavioral intentions under the mediation of cognitive bias and perceived risk, using S-O-R model and theory of behavioral finance. Employing a quantitative approach, data was collected through survey responses from 402 GenZ investors. The data was analysed using SmartPLS4 for PLS-SEM. The study evaluates the effectiveness of investor protection measures and contrasts modern finance theories, which assume market efficiency with behavioral finance theories highlighting the influence of psychological factors on behavioral intentions. The findings reveal that investor protection measures which include financial literacy, regulatory effectiveness, and surveillance deterrence, significantly influence behavioral intentions of GenZ investors. These factors have both direct and indirect effects with cognitive biases and perceived risk serving as mediators. This study is among the first to uniquely integrate investor protection measures with theory of behavioral finance. It empirically demonstrates that internal cognitive factors and external regulatory factors are crucial in shaping behavioral intentions of genZ investors.